ANALISIS PERSEPSI DAN PARTISIPASI MASYARAKAT PESISIR PADA PENGELOLAAN KKLD UJUNGNEGORO KABUPATEN BATANG - DIAN AYUNITA NND; TRISNANI DWI HAPSARI (Universitas Sebelas Maret, 2012)
In Batang Regency coastal area was a coastal management area program used conservation approach called “Marine Region Conservation Area (KKLD)”. Ujungnegoro coastal area located in Ujungnegoro Village, Kandeman District, Batang Regency. KKLD condition that officially formed by Batang Regent since 2005 is still undeveloped. Purposes of this research were to assess perception and people’s participation and also analyze correlation between perception and people’s participation in Ujungnegoro KKLD management. Purposive sampling was used tochoose respondents. Variables were perception and people’s participation of Ujungnegoro people’s.